Case Report: Women, Be Aware that Your Vocal Charisma can Dwindle in Remote Meetings - Siegert, Ingo; Niebuhr, Oliver (Frontiers in Communication, 2021)
Remote meetings via Zoom, Skype, or Teams limit the range and richness of nonverbal communication signals. Not just because of the typically sub-optimal light, posture, and gaze conditions, but also because of the reduced speaker visibility. Consequently, the speaker’s voice becomes immensely important, especially when it comes to being persuasive and conveying charismatic attributes. However, to offer a reliable service and limit the transmission bandwidth, remote meeting tools heavily rely on signal compression. It has never been analysed how this compression affects a speaker’s persuasive and overall charismatic impact. Our study addresses this gap for the audio signal. A perception experiment was carried out in which listeners rated short stimulus utterances with systematically varied compression rates and techniques. The scalar ratings concerned a set of charismatic speaker attributes. Results show that the applied audio compression significantly influences the assessment of a speaker’s charismatic impact and that, particularly female speakers seem to be systematically disadvantaged by audio compression rates and techniques. Their charismatic impact decreases over a larger range of different codecs; and this decrease is additionally also more strongly pronounced than for male speakers. We discuss these findings with respect to two possible explanations. The first explanation is signal-based: audio compression codecs could be generally optimized for male speech and, thus, degrade female speech more (particularly in terms of charisma-associated features). Alternatively, the explanation is in the ears of the listeners who are less forgiving of signal degradation when rating female speakers’ charisma.